2020
DOI: 10.3390/ph13110406
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Immunopathogenic and Therapeutic Roles of Granulocyte Colony-Stimulating Factor in Cancer

Abstract: Tumor cells are particularly adept at exploiting the immunosuppressive potential of neutrophils as a strategy to achieve uncontrolled proliferation and spread. Recruitment of neutrophils, particularly those of an immature phenotype, known as granulocytic myeloid-derived suppressor cells, is achieved via the production of tumor-derived granulocyte colony-stimulating factor (G-CSF) and neutrophil-selective chemokines. This is not the only mechanism by which G-CSF contributes to tumor-mediated immunosuppression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…Although many of the inhibitory actions of G-CSF on T cells are secondary effects caused by the regulation of other cell types, it has been reported that G-CSF directly controls T cell function. 25 , 33 To examine whether these direct effects impact anti-BCMA CAR-T cell activity, T cells were cultured for 3 days in the presence of recombinant G-CSF prior to activation, ARI2h CAR transduction, and cell expansion ( Figure 1 A). The efficacy of the recombinant G-CSF was tested by analyzing G-CSF-induced STAT3 phosphorylation in monocytes ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many of the inhibitory actions of G-CSF on T cells are secondary effects caused by the regulation of other cell types, it has been reported that G-CSF directly controls T cell function. 25 , 33 To examine whether these direct effects impact anti-BCMA CAR-T cell activity, T cells were cultured for 3 days in the presence of recombinant G-CSF prior to activation, ARI2h CAR transduction, and cell expansion ( Figure 1 A). The efficacy of the recombinant G-CSF was tested by analyzing G-CSF-induced STAT3 phosphorylation in monocytes ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was important to study the effect of G-CSF in vivo , as well as in vitro , because G-CSF-mediated regulation of other immune cell types, such as dendritic cells, 40 monocytes, 41 and myeloid-derived suppressor cells (MDSCs), 42 also causes T cell suppression. 33 For example, increased MDSC mobilization to the peripheral blood promotes abnormalities in the T cell compartment, such as reduced proliferation and polarization of CD4 + cells from a Th1 phenotype towards a Th2 phenotype. 43 , 44 Moreover, the increased presence of histocompatibility leukocyte antigen DR isotype (HLA-DR) −/low CD33 + CD16 − MDSCs in peripheral blood causes T reg expansion, 44 highlighting the complex interplay between G-CSF and a wide range of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of DCBM as a manifestation of a metachronous recurrence of cured cancer is unclear, recent studies have indicated the reactivation of dormant DTCs by various factors, which are mainly related with angiogenesis and the immunologic antitumor surveillance system[ 19 - 23 ]. The administration of G-CSF has been reported to be one of the factors that can promote cancer progression and invasion in various cancers[ 24 ], and this interaction was confirmed in vivo using gastric cancer cells expressing G-CSFR[ 25 ]. However, previous clinical documentations have seldom documented that G-CSF could trigger recurrence of cured malignancies.…”
Section: Discussionmentioning
confidence: 98%
“…However, no significant difference was detected for the incidence of leukopenia and neutropenia 12 months after chemotherapy between the long-acting and the short-acting groups. PEG-rhG-CSF and rhG-CSF have the same mechanism of action: G-CSF binds to G-CSF receptors expressed on hematopoietic cells to stimulate the proliferation of hematopoietic progenitor cells and accelerate the transformation of immature metamyelocytes into mature neutrophils, thereby increasing functional neutrophils in circulating peripheral blood ( 46 , 47 ). Compared with rhG-CSF, PEG-rhG-CSF can decrease plasma clearance and prolong half-life ( 15 ).…”
Section: Discussionmentioning
confidence: 99%